Soluções radiais para uma classe de equações de Hénon - Rodrigues, Caio Ilan Ferreira (2015)
In this work, we demonstrate the existence of radial solution for a class of problems related to Dirichlet Hénon equation. We present problems involving both the subcritical case as critical. To obtain our results, we use essentially the Radial Lemma, the Compactness Lemma, the Principle of Symmetric Criticality of Palais, the Mountain Pass Theorem and the Lagrange Multiplier Theorem.